Vazões de aplicação de solução nutritiva, teor de nitrato em alface sob cultivo hidropônico e aceitabilidade sensorial - Furtado, Lucia de Fatima (2008)
This study objective was to evaluate letuce (Lactuca sativa L cv. Vera) production and nitrate acumulation on its foliage under an environment protected by the Nutrient Film Technique (NFT) hidroponic system due to discharge of nutritive solution aplication and sensorial acceptability among conventional, organic, and hidroponic systems. Treatment was made of nutritive solutions combinned with three discharge aplications on the cultivated channels. Nutrient Solution was prepered according to FURLANI et al. (1999) which presents electric conductivity of 1.2 ms.cm. Aplication discharge were 0,5, 1,0 e 1,5 L.min-1. To evaluate the effect of treatments in the developing of the culture, data was submited to variance analisys (F test), and the results were evaluated through Tukey s average test (5%). Statistical delineament was casual with three treatments and eight repetitions. Each experimental unit comprised of eight heads of lettuce totaling 192 analized plants. Total fresh biomass, aereal fresh biomass, root fresh biomass, trunk fresh biomass, total dry biomass, aereal dry biomass, root dry biomass, and trunk dry mass were the evaluated caracteristic. It was concluded that the best discharge was 1.5 L.min-1, followed by 1.0 L.min-1 and last 0.5 L.min-1. As for nitrate ammount, analisys was done through spectrophotometry with samples of a plant for each analisys, and then avarege was taken between both analyses. There was no important differences to the level of 5% of significance. Organoleptic conditions were analized by the hedonic scale. Samplings originated from three cultivation systems: hidrophoinoc conventional and organic. Treatment was the three diferent culture systems, and repetirions were portions of aproximatly 20g of letuce from each system. Sensorial analysis results were interpreted through a variance analysis and an average comparison by the Tukey test showing the significant differences between the analyzed parameters such as appearance, flavor, texture, color, and global quality, but it did not present significant difference on the scent attribute. The organic system showed the best average considering global quality of 7.6, approximating the category Liked a lot. The hydroponic cultivar showed an average of 7.5, which also approximate the category Liked a lot. The organic method showed to be the best followed by the hydroponic method, where there were no significant difference in most attributes between the two cultivars, however, there were important differences to the 5% level of significance placing soil cultivation in last on consumer preference Scent.